Development of an Effective Method for the Determination of p-Hydroxybenzoic Acid Esters (Parabens) Surface Sediment in To Lich River - Anh, Dao Duy; Nguyen, Ta Thuy; My, Nguyen Nu Ha; Chau, Chu Ngoc; Long, Dang Van; Anh, Hoang Quoc; Minh, Tu Binh; Tri, Tran Manh (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4, 2025)
This study developed a method for the simultaneous determination of seven paraben compounds in sediment samples using liquid chromatography-tandem mass spectrometry (LC-MS/MS) combined with solid-phase extraction (SPE). Parabens were separated on a C 18 -column (Kinetex: 150 mm x 2.1 mm, 2.6 µm), with mobile phases (A): 0.05% acetic acid and (B): methanol. One hundred nanograms of each surrogate standard, 13 C-methylparaben ( 13 C-MeP) and  13 C-butylparaben ( 13 C-BuP), were added to 500 mg of freeze-dried sediment sample. Parabens were then ultrasonically extracted for 10 min with 5 mL of methanol/acetonitrile (1/1, v/v) acidified to pH~3 by formic acid. The sample was centrifuged at 4500 rpm for 5 min, and the supernatant was transferred to a glass tube. The extraction procedure was repeated twice. The extracted solution was then concentrated to ~1.5 mL under a gentle stream of nitrogen. The sample was then added with 10 mL of ultra-pure water and passed through an SPE column (Oasis HLB 500 mg), which had been activated respectively with 3 mL of methanol and 3 mL of ultra-pure water. The target compounds were eluted with 5 mL of methanol. The eluted solution was concentrated to 1 mL under a stream of nitrogen. The final solution was filtered through a Whatman filter paper (pore size: 0.2 µm) and analyzed on an LC-MS/MS instrument. Calibration curves of the native compounds were constructed in the concentration range of 0.5–200 ng/mL (R 2 > 0.997). The recoveries of the surrogate standards 13 C-MeP and 13 C-BuP were in the range of 85.5–105% (RSD < 9.5%) and 88.0–110% (RSD < 8.0%), respectively. The method detection limits of parabens in sediment samples ranged from 0.027 to 0.067 ng/g, corresponding to a quantification limit value of 0.07 to 0.19 ng/g. The standardized method was applied to determine the distribution of parabens in sediment samples collected from To Lich River, Hanoi. Total concentrations of parabens in sediment samples ranged from 12.5 to 81.9 ng/g.